A Political Economy of Public Policymaking and Underdevelopment in Postcolonial African States: A Marxian Perspective - Masumbe, Peter Sakwe (Advances in Social Sciences Research Journal, 2023)
Debates over who makes public policy in postcolonial African states are lengthy, spanning from 1960s until now, even as such debates prompt pernicious human underdevelopment in this region. Driven by these unfinished debates’ impervious outcomes - the impoverishment of postcolonial Africans, this paper uses the Marxian political economy perspective to determine the mischievous insights arising from these debates, which prod irrational policymaking. It argues that, although policymaking is par excellence the impeccable and inescapable normal government activity and an important political instrument for exerting exhilarating or doldrums societies, it is fraught with inequitably precarious, intricate and dispute-prone processes for mobilising, distributing and allocating resources in societies. Consequently, the paper examines this activity’s shortcomings, not only through the cognitive capacities or incapacities of government officials, but through subjective irrational groups’ interests. Using the rational-comprehensive theory of policymaking, it concludes that, even as policymaking is estranged by malicious contestations through soft or hard power from competing forces with undemocratic claims over rights and resources, the Marxian political economy perspective and rational-comprehensive model can dependably ensure the region’s equitable development rather than underdevelopment.